PENGARUH UMUR INDUK TERHADAP FERTILITAS, SUSUT TETAS, DAYA TETAS, DAN BOBOT TETAS TELUR KALKUN - Fredy Widiatmoko; Tintin Kurtini; Khaira Nova (JURNAL ILMIAH PETERNAKAN TERPADU, 2014)
Turkey meat has a high protein and low fat when compared with some other animal meat.Breeding companies commonly use hen age variation to maintain the availability of seed, hen agevariations lead to differences in performance hatching (fertility, weight loss, hatchability, andhatching weight). This study aims to: (1) determine the effect of hen age on fertility, weight loss,hatchability, and hatching weight of turkeys egg, (2) determine the best hen age of the on fertility,weight loss, hatchability, and hatching weight of turkeys egg. Research was conducted on March1 to April 12, 2013, held at the Mitra Alam Ranch Turkeys Partners Sukoharjo 1, DistrictSukoharjo, Pringsewu District. Eggs used are turkey eggs as much as 72 points. This research usedCompletely Randomized Design (CRD), with three treatments, namely P1 (egg from 9 months ofhen age), P2 (egg from11 months of hen age), and P3 (egg from 13 months of hen age). Thetreatment was repeated 6 times, and each experiment each unit consists of 4 eggs. Results of thisstudy showed that hen age was not a real is different (P> 0.05) on fertility, weight loss, andhatchability. However, the hen age showed significant differences (P <0.05) on hatching weight,and 13 month of hen age treatment gives the best effect on hatching weight.